Ethnic inequalities in health intervention coverage among Mexican women at the individual and municipality levels. (January 2022) - Armenta-Paulino, Nancy; Wehrmeister, Fernando C; Arroyave, Luisa; Barros, Aluísio J.D.; Victora, Cesar G.
Summary: Background: Using data from Mexico, the country with the largest indigenous population in Latin America, we describe ethnic inequalities in coverage with women's health interventions at individual and municipal levels. Methods: Cross-sectional study using data from the National Health and Nutrition Survey 2018 and the Mexican Intercensal Survey 2015. We selected five outcomes: modern contraceptive use, content-qualified antenatal care (ANCq), and skilled birth attendant (SBA) for women aged 15–49 years; Pap smear test and mammogram among women aged 25-64 and 40-69 years respectively. Municipalities were classified into three groups by the percentage of indigenous population: <10%, 10% – 39%, and ≥40%. We calculated crude and adjusted coverage ratios (CR) and 95% confidence intervals (CI) using Poisson regression. Findings: Women living in municipalities with indigenous population ≥40% were poorer, less educated, and more rural. Coverage was lower for indigenous than non-indigenous for modern contraceptive use (CR: 0·73; CI 0·65-0·83), ANCq (CR: 0·72; CI 0·62-0·83), SBA (CR: 0·83; CI 0·77-0·90) and undergoing a mammogram (CR: 0·54; CI 0·41-0·71), but not for Pap smears (CR: 0·94; CI 0·83-1·07). Coverage with the five interventions increased as the municipal proportions of indigenous population decreased, both for indigenous and non-indigenous women. Coverage gaps at municipal level tended to be wider than at individual level. Interpretation: Both indigenous and non-indigenous women living in municipalities with high proportions of indigenous people were systematically excluded from reproductive and maternal interventions. Our findings suggest that social and health interventions targeted at the individual level should be complemented by structural interventions in municipalities with high proportions of indigenous people, including strengthening health and social services.